The early adoption of intensity‐modulated radiotherapy and stereotactic body radiation treatment among older Medicare beneficiaries with prostate cancer. Issue 15 (16th March 2017) - Jacobs, Bruce L.; Yabes, Jonathan G.; Lopa, Samia H.; Heron, Dwight E.; Chang, Chung‐Chou H.; Schroeck, Florian R.; Bekelman, Justin E.; Kahn, Jeremy M; Nelson, Joel B.; Barnato, Amber E.
Abstract : BACKGROUND: Several new prostate cancer treatments have emerged since 2000, including 2 radiotherapies with similar efficacy at the time of their introduction: intensity‐modulated radiotherapy (IMRT) and stereotactic body radiation therapy (SBRT). The objectives of this study were to compare their early adoption patterns and identify factors associated with their use. METHODS: By using the Surveillance, Epidemiology, and End Results (SEER)‐Medicare database, patients who received radiation therapy during the 5 years after IMRT introduction (2001‐2005) and the 5 years after SBRT introduction (2007‐2011) were identified. The outcome of interest was the receipt of new radiation therapy (ie, IMRT or SBRT) compared with the existing standard radiation therapies at that time. The authors fit a series of multivariable, hierarchical logistic regression models accounting for patients nested within health service areas to examine the factors associated with the receipt of new radiation therapy. RESULTS: During 2001 to 2005, 5680 men (21%) received IMRT compared with standard radiation (n = 21, 555). Men who received IMRT were older, had higher grade tumors, and lived in more populated areas ( P < .05). During 2007 through 2011, 595 men (2%) received SBRT compared with standard radiation (n = 28, 255). Men who received ng SBRT were more likely to be white, had lower grade tumors, lived in more populated areas, and were more likely to live in the Northeast ( P < .05). Adjusting for cohort demographic and clinical factors, the early adoption rate for IMRT was substantially higher than that for SBRT (44% vs 4%; P < .01). CONCLUSIONS: There is a stark contrast in the adoption rates of IMRT and SBRT at the time of their introduction. Further investigation of the nonclinical factors associated with this difference is warranted. Cancer 2017;123:2945–54. © 2017 American Cancer Society . Abstract : There is a stark contrast in the adoption rates of intensity‐modulated radiotherapy and stereotactic body radiation treatment for prostate cancer at the time of their introduction. Further investigation of the nonclinical factors associated with this difference is warranted.